Atlas of 5'P mRNA decay in bacteria - Huch, Susanne; Nersisyan, Lilit; Ropat, Maria; Barrett, Donal; Wu, Mengjun; Wang, Jing; Valeriano, Valerie D; Vardazaryan, Nelli; Huerta-Cepas, Jaime; Wei, Wu; Du, Juan; M Steinmetz, Lars; et al. (Karolinska Institutet, 2023)
Regulation of mRNA stability is a central process in gene expression. Here, report an atlas of 5´ monophosphorylated mRNA decay intermediates (5´P) in 96 species. We use those data to demonstrate that in species with 5´-3´exonuclease activity, the exoribonuclease RNase J follows the trailing ribosome, producing an in vivo single-nucleotide toeprint of its 5´ position. While in other species, ribosome position alters endonucleolytic cleavage sites. Our work demonstrates the universal connection between RNA decay and translation and paves the way for use of metadegradome sequencing to investigate post-transcriptional regulation of unculturable species present and complex microbial communities.

Data was analyzed using our fivepseq software.  Improved computational analysis of ribosome dynamics from 5′P degradome data using fivepseq (https://doi.org/10.1093/nargab/lqaa099) . Lilit Nersisyan, Maria Ropat & Vicent Pelechano. NAR Genomics and Bioinformatics, Volume 2, Issue 4, December 2020, lqaa099, https://doi.org/10.1093/nargab/lqaa099
Keywords: Microbial genetics; Genomics and transcriptomics; Gene expression (incl. microarray and other genome-wide approaches); Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik